IMPROVING THE CONTENT OF METHODOLOGICAL RECOMMENDATIONS FOR THE PRACTICAL APPLICATION OF PROSPECTIVE POSITIONAL AND METRIC PROBLEMS (International journal of artificial intelligence, 2025)
This paper analyzes the theoretical foundations and practical applications of positional and metric problems. It focuses on improving the content of methodological recommendations through a comparative study of existing approaches and the development of more efficient algorithms. Practical experiments demonstrate the effectiveness of the proposed improvements in real-world scenarios.